The ledge plant communities in a limestone cave of the Apuan area: identification and survey by UAV technology - Andrea Bertacchi; Diego Orazi; Leonardo Ercolini (Italian Botanist, 2025)
The Apuan Alps are a mountain range in the north-west of Tuscany, part of the Tuscan Sub-Apennines. The particular geomorphology, exposure, and biogeographic location create a diversified vegetation landscape across altitudinal and latitudinal gradients. The sclerophyllous formations of the Mediterranean scrub and woods of the maritime side coexist with mesophilous broadleaf woods and grasslands at higher elevations. In this context, it is possible to find heterotopic patches of evergreen sclerophyllous vegetation in the inner mountain complex, closely linked to the external walls of limestone reliefs. These sites, often characterized by superficial and deep karst phenomena, reveal the presence of underground cavities frequented by humans since the post-glacial period. This article presents a case study involving field surveys and UAV (Unmanned Aerial Vehicle) technology in a limestone cave near Tenerano (Massa-Carrara, Tuscany), to identify the species and the plant communities of the site for a historical reconstruction of the natural plant landscape.